Bangladesh Integrated Household Survey (BIHS) 2015 - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Bangladesh that collects detailed data on (1) plot-level agricultural production and practices, (2) dietary intake of individual household members, (3) anthropometric measurements (height and weight) of all household members, and (4) data to measure women’s empowerment in agriculture index (WEAI). A community survey supplements the BIHS data to provide information on area-specific contextual factors. The BIHS covers 6500 households in 325 primary sampling units. The sample is statistically representative at following levels: (a) nationally representative of rural Bangladesh; (b) representative of rural areas of each of the seven administrative divisions of the country: Barisal, Chittagong, Dhaka, Khulna, Rajshahi, Rangpur, and Sylhet; and (c) representative of the Feed the Future (FTF) zone of influence. The first round of survey can be accessed at http://hdl.handle.net/1902.1/21266.